Kinetic Light Shelf Design And The Impacts On Daylighting Performance In Tropical Climate - Bahdad, Ali Ahmed Salem (2021)
This research aims to introduce an optimized office workspace that meets the sufficient daylight availability by using a manually controlled kinetic light shelf system. This research determines the light-shelf controlled parameters that can be manually adjusted and are applicable under tropical climate according to these variables: modified horizontal locations, height positions, external and internal parts depth, and external and internal parts tilt angles.